Pengaruh Product Quality dan Online Brand Community Terhadap Brand Attitude Sepatu Compass - Nabila Elyana Putri; Vina Meliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of product quality, and online brand community on brand attitude for compass shoes located in DKI Jakarta. This type of research used in this study is to use quantitative methods. In this study, researchers used quantitative data from the results of distributing questionnaires directly to respondents or through Google forms. The sample of this study was 150 respondents who were respondents who knew the brand of compass shoes, had bought a compass shoe for the first time in 2020 and knew the compass brand from the online compass community, @ temancompass.co on Instagram. The results of observations were analyzed with data analysis techniques used are multiple regression and it can be concluded that product quality has a influence on brand attitude, online brand community has a influence on brand attitude, and the product quality and online brand community together influence the brand attitude.